2012
DOI: 10.1021/ac201767g
|View full text |Cite
|
Sign up to set email alerts
|

Robust Data Processing and Normalization Strategy for MALDI Mass Spectrometric Imaging

Abstract: Matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) provides localized information about the molecular content of a tissue sample. To derive reliable conclusions about MSI data, it is necessary to implement appropriate processing steps in order to compare peak intensities across the different pixels comprising the image. Here, we review commonly used normalization methods, and propose a rational data processing strategy, for robust evaluation and modeling of MSI data. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
159
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 38 publications
1
159
0
Order By: Relevance
“…Consequently the non-specific noise that is the principal contributor to a spectrum's TIC for MALDI-ToF instruments is absent. Fonville et al have investigated normalization under such conditions, using data acquired on a MALDI Q-ToF instrument [35]. They investigated the use of the total ion count of the picked peaks and also other normalization methods such as normalization to matrix-related peaks or informative peaks.…”
Section: Global Intensity Suppression and Normalizationmentioning
confidence: 99%
“…Consequently the non-specific noise that is the principal contributor to a spectrum's TIC for MALDI-ToF instruments is absent. Fonville et al have investigated normalization under such conditions, using data acquired on a MALDI Q-ToF instrument [35]. They investigated the use of the total ion count of the picked peaks and also other normalization methods such as normalization to matrix-related peaks or informative peaks.…”
Section: Global Intensity Suppression and Normalizationmentioning
confidence: 99%
“…The objectives of variance-stabilizing normalization are to remove biologically unrelated pixel-to-pixel variation in overall signal intensity and to convert multiplicative noise into additive noise for subsequent application of multivariate statistical techniques; i.e., vsn x kðixjÞ n ðixjÞ ≈ μ kðixjÞ + « kðixjÞ , [3] where vsn denotes a variance-stabilizing normalization, μ k(ixj ) is the transformed peak intensity, and « kðixjÞ is random additive noise. Here, the normalization factor has been estimated by calculating the median peak intensity, which we have shown is a more robust estimate compared with the widely cited TIC normalization method (21,23). Due to peak integration and noise-related peak filtration steps, it was assumed that the influence of background noise in the model (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…This reduces mass detection accuracy and introduces biologically irrelevant spectral features, making unambiguous assignment of chemical species more difficult. In the case of normalization, the total ion current (TIC) scaling factor is frequently cited in the literature as an acceptable means of accounting for global intensity changes in a MSI dataset (20)(21)(22). However, we have recently demonstrated that the performance of this method can be compromised by single large molecular ion peak intensities (21,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, computational methods for MSI data pre-processing, feature extraction, (tumor) tissue classification and spatial autocorrelation have been advanced [23][24][25][26][27][28][29][30][31][32][33][34], but most of them still focus on MS imaging of non-digested human FFPE or frozen tissue [24,29,[35][36][37][38][39][40]. Classification of human tumors based on digested FFPE tissue and MALDI MSI has been described, in seminal proof-of-concept studies, for pancreatic cancer [41] and prostate cancer [42].…”
Section: Introductionmentioning
confidence: 99%